Wind Power Fluctuation Suppression by Doubly-fed Variable-speed Pumped Storage Unit - Chao CHEN; Haibin LIU; Jing GE; Xuejun QIU; Lei CHEN; Xinbao WANG; Junbo FU (发电技术)
Due to the intermittent and fluctuant of wind power, large-scale wind power grid-connected poses a challenge to the safe and stable operation of the power grid. Therefore, a wind power fluctuation suppression control strategy based on doubly-fed variable-speed pumped storage unit was proposed. Firstly, based on DIgSILENT/PowerFactory software, the simulation models of doubly-fed variable-speed pumped storage unit under the conditions of power generation and pumping were established to verify its fast power control capability. Secondly, based on the principle of low-pass filtering, combined with the wind power prediction, the control models of the doubly-fed variable-speed pumped storage unit were established to suppress wind power fluctuation under the conditions of power generation and pumping. Finally, a simulation example was given to verify the control strategy. The results show that the doubly-fed variable-speed pumped storage unit has fast power response characteristics. Under the conditions of power generation and pumping, the fluctuation of wind power can be effectively suppressed, the regulation pressure of conventional units can be reduced, and the stability of regional power grid can be improved.